Computational study of β-N-acetylhexosaminidase from Talaromyces flavus, a glycosidase with high substrate flexibility - Kulik, Natallia; Slámová, Kristýna; Ettrich, Rüdiger; Křen, Vladimír (BMC bioinformatics, 2015)
BACKGROUND: β-N-Acetylhexosaminidase (GH20) from the filamentous fungus Talaromyces flavus, previously identified as a prominent enzyme in the biosynthesis of modified glycosides, lacks a high resolution three-dimensional structure so far. Despite of high sequence identity to previously reported Aspergillus oryzae and Penicilluim oxalicum β-N-acetylhexosaminidases, this enzyme tolerates significantly better substrate modification. Understanding of key structural features, prediction of effective mutants and potential substrate characteristics prior to their synthesis are of general interest. RESULTS: Computational methods including homology modeling and molecular dynamics simulations were applied to shad light on the structure-activity relationship in the enzyme. Primary sequence analysis revealed some variable regions able to influence difference in substrate affinity of hexosaminidases. Moreover, docking in combination with consequent molecular dynamics simulations of C-6 modified glycosides enabled us to identify the structural features required for accommodation and processing of these bulky substrates in the active site of hexosaminidase from T. flavus. To access the reliability of predictions on basis of the reported model, all results were confronted with available experimental data that demonstrated the principal correctness of the predictions as well as the model. CONCLUSIONS: The main variable regions in β-N-acetylhexosaminidases determining difference in modified substrate affinity are located close to the active site entrance and engage two loops. Differences in primary sequence and the spatial arrangement of these loops and their interplay with active site amino acids, reflected by interaction energies and dynamics, account for the different catalytic activity and substrate specificity of the various fungal and bacterial β-N-acetylhexosaminidases.
Keywords: simulace molekulární dynamiky; Kinetics; beta-N-Acetylhexosaminidases; fylogeneze; Structure-Activity Relationship; Talaromyces; výpočetní biologie; Phylogeny; beta-N-acetylhexosaminidasy; Sequence Homology, Amino Acid; molekulární sekvence - údaje; Amino Acid Sequence; Molecular Dynamics Simulation; sekvenční homologie aminokyselin; reprodukovatelnost výsledků; Reproducibility of Results; molekulární modely; vztahy mezi strukturou a aktivitou; Models, Molecular; substrátová specifita; kinetika; Catalytic Domain; Substrate Specificity; sekvence aminokyselin; Molecular Sequence Data; glykosylace; Glycosylation; katalytická doména; Computational Biology